2002
DOI: 10.1161/01.str.0000014582.03429.f7
|View full text |Cite
|
Sign up to set email alerts
|

Angioarchitectural Factors Present in Brain Arteriovenous Malformations Associated With Hemorrhagic Presentation

Abstract: Background and Purpose-Associations between clinical presentation of brain arteriovenous malformations (AVMs) and their angioarchitecture have been described. This study aims to identify significant factors related to the initial hemorrhagic event through multivariate statistical methodology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
86
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(102 citation statements)
references
References 24 publications
7
86
0
1
Order By: Relevance
“…[1][2][3][4][5][6][7][8] In AVMs presenting with intracranial hemorrhage, better recognition of certain angioarchitectural features of the AVM as likely weak spots prone to recurrent hemorrhage, such as intranidal-and flow-related aneurysms and venous stenoses, has prompted many operators to perform a partial targeted embolization treatment when complete AVM obliteration is unlikely or impossible. [9][10][11][12][13][14] The growing experience with the use of Onyx in our department together with advancement in imaging possibilities and the adjustment of the technique of curative embolization have gradually resulted in the adaptation of the treatment paradigm of patients with AVMs in our hospital. Embolization is no longer basically restricted to partial nidus obliteration of large AVMs to facilitate subsequent surgery or radiosurgery.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] In AVMs presenting with intracranial hemorrhage, better recognition of certain angioarchitectural features of the AVM as likely weak spots prone to recurrent hemorrhage, such as intranidal-and flow-related aneurysms and venous stenoses, has prompted many operators to perform a partial targeted embolization treatment when complete AVM obliteration is unlikely or impossible. [9][10][11][12][13][14] The growing experience with the use of Onyx in our department together with advancement in imaging possibilities and the adjustment of the technique of curative embolization have gradually resulted in the adaptation of the treatment paradigm of patients with AVMs in our hospital. Embolization is no longer basically restricted to partial nidus obliteration of large AVMs to facilitate subsequent surgery or radiosurgery.…”
mentioning
confidence: 99%
“…Fults and Kelly 12 noted that less than half of their patients with posterior fossa AVMs survived an initial hemorrhage, and hemorrhagic mortality rates of up to 66.7% have been reported for posterior fossa AVM rupture. 34 In addition to the aforementioned surgical series, numerous recent observational studies have also demonstrated the greater rate of hemorrhagic presentation among patients with these lesions, 11,17,28,32,39 with only a few exceptions. 9,20,22 In a multivariate analysis targeted at elucidating the relationship between infratentorial location and hemorrhagic presentation, Khaw et al 19 demonstrated that infratentorial AVMs were almost twice as likely to present with hemorrhage as supratentorial AVMs.…”
mentioning
confidence: 99%
“…[16][17][18][19] Better recognition of certain angioarchitectural features of the AVM as likely weak spots prone to recurrent hemorrhage, such as intranidal-and flow-related aneurysms and venous stenoses, have prompted many operators to perform a partial targeted embolization treatment when complete AVM obliteration is unlikely or impossible. 7,[11][12][13][14][15] Intranidal-and flow-related aneurysms can be excluded from the circulation with Onyx, acrylic glue, or coils, and venous outflow restrictions can be exonerated by occlusion of high-flow intranidal fistula with Onyx under flow arrest with a microballoon. 21 These new developments in the treatment of brain AVMs, in combination with the concurrent and similar advancement of endovascular treatment with Onyx of dural arteriovenous fistulas with drainage to the cortical veins, 22,23 have led our hospital to an adaptation of the diagnosis and treatment strategy in patients with hemorrhagic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Specific elimination of these weak spots or reduction of flow through the AVM by endovascular or surgical therapy is thought to decrease the rate of repeated hemorrhage and to improve prognosis, even when the AVM is only partially obliterated. [11][12][13][14][15][16] With modern endovascular techniques, targeted treatment of AVM-associated aneurysms, partial nidus obliteration with flow reduction, or complete obliteration is possible in most patients with AVMs. [16][17][18][19] In this article, we evaluate the results of a treatment strategy for brain AVMs that present with hemorrhage that includes early angiographic diagnosis and endovascular treatment in the acute phase.…”
mentioning
confidence: 99%